Chapter 11 The Pathos of the Soldier-Athlete in Japanese Memories of the Asia-Pacific War - Seaton, Philip (Taylor & Francis, 2023)
Within Japan's contested memories of the Asia-Pacific War (1937-45), the depiction of soldiers, sailors and pilots in leading roles within cinematic/televisual representations of the war usually falls into one of three main patterns: 'military heroes' participating in a noble (albeit losing) war; 'good Japanese' facing down villainous militarists; and 'victim-heroes' suffering amidst the uncontrollable carnage of war. A recurrent trope, particularly within the representation of 'victim-heroes', is a focus on the soldier's life and/or talents away from the military: the soldier as artist, scholar, lover, and athlete. Through a short history of sport in wartime Japan and six case studies of soldier-athletes - two with 'inconvenient life histories', two with 'usable life histories', and two (semi-)fictionalized characters - this chapter establishes how sport is used to humanize soldier characters and thereby pull the overall narrative of the film towards a pacifist message of the inhumanity of and suffering during war.